AN EXPERIMENTAL STUDY ON THE EFFECT OF PARTS STRATEGY AND ANXIETY ON READING COMPETENCY AT THE ELEVENTH GRADE STUDENTS OF SMAN 5 DENPASAR - Lindawati, P.; Tantra, D.K.; Ratminingsih, M. (International Journal of Language and Literature, 2017)
The aim of this study was to prove whether the implementation of PARTS Strategy and the studentsâ anxiety gave a significant effect to the studentsâ reading competency. The study was an experimental study by applying Post test only control group design. The population was nine classes (420 students) of grade XI in SMA Negeri 5 Denpasar academic year 2012/2013, in which 2 classes were samples which were assigned into two groups, i.e. experimental group and control group, by a Multi-Stage Random Sampling. The research data were collected through questionnaire and test that were analyzed using Statistical Two-Way Anova. The results show that, first, there wasÂ  different effect in reading competency between the students who were taught by implementing PARTS strategy and those who were taught by implementing Conventional reading startegy (Sig.=0.004 <=0.05). Secondly, there was not interactional effect of PARTS strategy andÂ  anxiety level upon the studentsâ reading competency at the eleventh grade students of SMA negeri 5 Denpasar (Sig.=0.966 >=0.05). In view of the results of this study, it is therefore suggestedÂ  that teachers should use PARTS Strategy as an innovative teaching strategy since the facilitation of this strategy significantly improved the studentsâ reading competency.